Family support in postpartum perineal wound care from a cultural perspective: A qualitative study - Diana Ulfah; Yani Marlina (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Postpartum mothers undergoing vaginal delivery face a significant risk of perineal trauma, a condition with a high global prevalence (2.7 million cases in 2020, with 75% of the incidence in Indonesia) that, if not managed properly, can lead to serious complications such as infection, prolonged pain, and sexual dysfunction, exacerbated by the anatomical reality of persistent exposure to lochia moisture. Effective recovery fundamentally relies on crucial factors including hygiene, nutrition, and early mobilization, yet the role of family support a key determinant in decision-making and practical care remains underexplored, particularly in the highly multicultural context of Indonesia. This cultural perspective is crucial because local traditions and beliefs often introduce dietary or activity taboos that directly impact healing. Therefore, to address the common morbidity associated with perineal wounds and the recorded perineal rupture rate of 54% in regions such as West Java, this qualitative study is urgently needed to address the knowledge gap by in-depth exploring: